Evaluation of Nutritional Status by Mid-Upper Arm Circumference Amongst Affluent Children - Maiti, S; De, D; Ali, KM; Ghosh, A; Ghosh, Debidas; Paul, S (Journal of Nepal Paediatric Society, 2012)
Introduction: Anthropometry is widely accepted as low-cost technique for defining the nutritional status of children. The mid upper arm circumference (MUAC) is a fast screening method in detecting acute malnutrition and it is also a predictor of childhood mortality. Materials and Methods: This is the retrospective study to evaluate the nutritional status based on mid upper arm circumference (MUAC) among urban, pre-school age children. A total of 1060 children, aged 1 to 3 years, attending the vaccination clinic of the Indian Red Cross Society Paschim Medinipur Hospital over a two years period, were enrolled in the study. The measurement of MUAC (in centimetres) was taken by the standard technique. Undernutrition was defined based on age and sex-specific MUAC cut-off values as recommended by the World Health Organization (WHO). Results: Boys were higher level of mean MUAC than girls at all ages and there was no significant sex differences. The age-combined rate of overall undernutrition was 18.96% and it was slightly higher among the boys (19.38%) than girls (18.46%). The age-combined moderate undernutrition was higher among the boys (16.08% vs 14.11%) but girls’ value was higher in case of severe undernutrition (3.28% vs 4.35%). Conclusion: The present study showed that a remarkable number of pre-schooler was undernourished based on MUAC. J. Nepal Paediatr. Soc. 32(2) 2012 113-116 doi: http://dx.doi.org/10.3126/jnps.v32i2.5689